The Last Queens of Egypt - Sally-Ann Ashton (UK Pearson, 2003)
"The Last Queens of Egypt provides a fascinating look at Cleopatra's ancestors, the Ptolemaic queens, and offers an insight into one of Egypt's most famous but enigmatic families. At first glance the Ptolemaic queens appear to represent liberated and powerful individuals. A further investigation of their history and presentation, however, reveals that they were often used and abused by their consorts, brothers and sons. The role of queen was in many respects a kiss of death." --Book Jacket
Keywords: History, Geography and Archaeology (3GdJGQjN hGdLZQGajG hGdBKGQs; Queens -- Egypt -- History; Queens -- Egypt -- Biography; General